The Control of Energy Metabolism in the Yeast Saccharomyces Cervisiae - Ball, John Stuart Alan (My University, 1969)
The yeast S. cerevisiae Is able to use several different metabolic pathways for the generation of metabolic energy, and is able to vary the synthesis of these multlenzyme systems in response to changes in the external environment. The responses of the yeast to various changes in the environment have been studied and correlated with changes in the rate of synthesis of various enzymes. Two of these pathways are found in the mitochondrion, a sub-cellular organelle, the structural integrity of which is necessary for the functioning of these integrated systems. The experiments described thus provide information about the control of structure and function in cellular organelles, as well as about the general changes in energy metabolism.
Department not listed. Molecular Biology
Keywords: molecular biology; yeast; metabolism; energy; control; Biology; Pathogenic Microbiology; Biology